PENGARUH KECERDASAN INTELEKTUAL, MOTIVASI, DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI BADAN KEUANGAN DAN ASET DAERAH KABUPATEN MAJENE - Fahmi Syarif; Ahmad Firman; Saripuddin D (Nobel Management Review, 2020)
The research aims to determine and analyze the effect of intellectual intelligence, motivation and work culture individually and jointly on the performance of employees at the Regional Finance and Assets Agency in Majene Regency.The design of this study uses survey research that takes samples from one population and uses questionnaires as a primary data collection tool. The study was conducted at the Regional Finance and Assets Agency in Majene Regency. The time of the study was from November to December 2019. The population in the study were all employees of the Majene Regency Financial and Asset Agency, amounting to 97 people. The sampling technique used in this study is census sampling or saturated sample, which is the total sample is all population. The number of samples in this study were 97 respondents. Data analysis using multiple regression analysis (multiple regression analysis).The results showed that intellectual intelligence, motivation and work culture each had an influence on the performance of Majene Regency's Financial and Asset Agency employees. The variables in this study indicate that motivation is more dominantly influencing the performance of Majene Regency's Financial and Asset Agency employees.